A diagnostic study of cyclogenesis in the lee of the Alps. - Mcginley, John A. (My University, 1981)
Evaluation of energy transformations show that mean kinetic energy^within the volume (K), is converted to perturbation kinetic energy (K'), (' )^during the orographic phase. Mean available potential energy (A), is(' )^converted to perturbation available potential energy (A'), during the^frontal strengthening phase. During rapid development, barotropic(, )^processes (K (--->) K') dominate the baroclinic processes (A' (--->) K'), however both contribute to development. During the transition stage, (A' (--->) K') is the primary conversion although barotropic processes still play a role in increasing K'.

The lee cyclone passes through distinct stages during its life. These are: (1)Orographic stage, which is related to conservation of potential vorticity and production of shallow circulations. (2)Rapid development stage, where dynamically forced upward motion and terrain produced downward motion combine to concentrate vorticity at middle levels. (3)Transition stage, where increased thermal advection and movement away from the mountains allows the storm to grow baroclinically.

The blocking effect on the cooler air and externally forced vertical motions are shown to increase the mean frontal zone strength as the wave interacts with the Alps.

Rawinsonde and satellite data are assimilated in a three dimensional analysis scheme which couples mass and momentum, and allows computation of vertical motion. This scheme is used to diagnose the characteristics of cyclone development in the lee of the Alps. By allowing the dimensions of the terrain and the data to define the appropriate magnitude of ageostrophic flow and vertical scale, we can obtain horizontal and vertical motion fields which reflect the proper ratio of flow around versus over the Alps. Using quasi-Lagrangian volumes moving with the upper wave and associated baroclinic zone, the evolution of frontal strength, vorticity, and energy is examined for two lee cyclone episodes.
Keywords: Physics, Atmospheric Science.